PERBEDAAN PERAWATAN TALI PUSAT DENGAN MENGGUNAKAN KASSA STERIL, KASSA BETHADINE DAN KASSA ALKOHOL DENGAN LAMANYA LEPAS TALI PUSAT BAYI - Bunga Soeharto; Murdiningsih; Putu Lusita Nati Indriani; Merisa Riski (LPPM STIKes Mitra Adiguna, 2023)
Treatment of the umbilical cord, including using alcohol, including still using povidone iodine and the use of sterile dry gauze. The purpose of the study was to determine the difference between umbilical cord care using sterile gauze, betadine gauze and alcohol gauze with the length of time the baby's umbilical cord was removed. The research design used descriptive observation. The population of this study were all newborns estimated at 30 people in the Poskesdes Working Area of ​​the Talang Pangeran Health Center. Samples were divided into 3 groups which were taken using accidental sampling technique. Data analysis using univariate analysis and bivariate analysis using one way ANOVA test. The results showed that the length of time for umbilical cord detachment for babies treated using sterile gauze was an average of 5.80 days, betadine gauze averaged 7.10 and alcohol gauze averaged 7.30 days. The conclusion is there is a difference in umbilical cord care using sterile gauze and betadine gauze with the length of time the baby's umbilical cord is removed (p value 0.030).